Social networks and natural resource management uncovering the social fabric of environmental governance - d; Prell, Christina; ebrary, Inc. (Cambridge ; New York : Cambridge University Press, 2011)
"The goal of this book is to outline how social network analysis can be used as a conceptual tool and an analytical method for uncovering a variety of social factors affecting resource governance, particularly as it is conceptualized by these more recent perspectives. We will therefore confine our discussion to adaptive co-management (hereafter ACM), in an attempt to show how this theory, and related concepts, are linked to other theories of importance for natural resource governance, and how social network analysis can help further our understanding in this domain. In doing this we do not suggest that ACM is necessarily better than other concept or theoretical frameworks available"--
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Natural resources -- Management; Social networks; Electronic books